Study of feasibility of laparoscopic inguinal hernia surgery in taiping hospital - Abu Hassan, Hasslinda (2010)
The history of inguinal hernia repair (IHR) has gone through many stages of development from the ancient era until today. Inguinal hernia repair is one of the commonest surgical procedure worldwide, irrespective of socioeconomic status or country. Today, with the advancement of laparoscopic surgeries, inguinal hernia has been listed as one of the preferred surgical condition repaired by laparoscopic approach. Nowadays, despite its known complications, advantages and disadvantages, Laparoscopic Inguinal Hernia Repair (LIHR) is widely accepted as the better option of treatment as compared to open approach of inguinal hernia repair (IHR).